Effect of Achieving Minimal Disease Activity on the Progression of Subclinical Atherosclerosis and Arterial Stiffness: A Prospective Cohort Study in Psoriatic Arthritis. Issue 2 (5th January 2019) - Cheng, Isaac T.; Shang, Qing; Li, Edmund K.; Wong, Priscilla C.; Kun, Emily W.; Law, Mei Yan; Yip, Ronald M.; Yim, Isaac C.; Lai, Billy T.; Ying, Shirley K.; Kwok, Kitty Y.; Li, Martin; et al.
Abstract : Objective: To investigate the effects of achieving minimal disease activity (MDA) on the progression of subclinical atherosclerosis and arterial stiffness in patients with psoriatic arthritis (PsA). Methods: A total of 101 consecutive patients with PsA were recruited for this prospective cohort study. All patients received protocolized treatment targeting MDA for a period of 2 years. High‐resolution carotid ultrasound and arterial stiffness markers were assessed annually. The primary outcome measure was the effect of achieving MDA at 12 months (MDA group) on the progression of subclinical atherosclerosis over a period of 24 months. Secondary objectives were to compare the changes in arterial stiffness markers over 24 months between the MDA and non‐MDA groups, as well as the changes in subclinical atherosclerosis and arterial stiffness markers in patients who achieved MDA at each visit from month 12 through month 24 (sustained MDA [sMDA]). Results: Ninety PsA patients (mean ± SD age 50 ± 11 years, 58% male [n = 52]) who completed 24 months of follow‐up were included in this analysis. Fifty‐seven patients (63%) had achieved MDA at 12 months. Subclinical atherosclerosis and arterial stiffness outcomes were similar between the MDA and non‐MDA groups. Forty‐one patients (46%) achieved sMDA. As shown by multivariate analysis, achieving sMDA had a protective effect on plaque progression (odds ratio 0.273 [95% confidence interval 0.088–0.846], P = 0.024), and less of an increase in total plaque area, mean intima‐media thickness, and augmentation index values after adjustment for covariates. Conclusion: Our results support the recommendation that once MDA is achieved, it should ideally be maintained for a prolonged period in order to prevent progression of carotid atherosclerosis and arterial stiffness in patients with PsA.